Single-cell RNA sequencing reveals TCR+ macrophages in HPV-related head and neck squamous cell carcinoma - Jiang, Yourong; Zhang, Siwei; Tang, Lu; Li, Rui; Zhai, Jinglei; Luo, Suisui; Peng, Yiman; Chen, Xiaohang; Wei, Lanlan (Frontiers in Immunology, 2022)
Abstract The prognosis of Human papilloma virus (HPV) infected head and neck cancer (HNSCC) is often better than that of HPV- cancer, which is possibly caused by the differences in their immune microenvironments. As a principal innate immune cell, the contribution of macrophage to this phenomenon is still unclear. In this study, a single-cell atlas of 4,388 high-quality macrophages from 18 HPV- and 8 HPV+ HNSCC patients was constructed with single-cell RNA sequencing data. 8 macrophage subsets were identified from HNSCC, while their functional properties and developmental trajectory were delineated based on HPV status. Our results demonstrated that macrophages in HPV+ HNSCC exhibit stronger phagocytic ability, though the infiltration rate of macrophages decreased. From the results, a unique macrophages subset with TCR and CD3-specific signatures was identified from HPV-related HNSCC. These TCR+ macrophages potentially participate in the regulation of TCR signaling pathway and phagocytosis. In conclusion, our results suggested that HPV could affect the infiltration rate, function, and differentiation of macrophages in HNSCC, while TCR+ macrophages play a critical role in HNSCC microenvironment. These results provide new insights into the immune microenvironment of HNSCC and offer a valuable resource for the understanding of the immune landscape of HPV related HNSCC, which will in turn help the development of immunotherapy strategies for the disease.